PENERAPAN METODE PEMBIASAAN PADA TANGGUNG JAWAB PESERTA DIDIK KELAS II DI MI KREATIF YAYASAN PESANTREN SABILIL MUTTAQIN (YPSM) MANGIRAN - Abu Zaeni (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
The habituation method is a way that can be done to make children accustomed to thinking, behaving, and acting in accordance with the teachings of Islam. This method is very suitable for the development and formation of the character of early childhood children in increasing a sense of responsibility, such as completing tasks at school or at home. The purpose of this study is to: 1) determine the forms of habituation methods on the responsibility of class II students at MI Kreatif Yayasan Pesantren Sabilil Muttaqin (YPSM) Mangiran, 2) Knowing the implementation of the habituation method on the responsibility of class II students at MI Kreatif Yayasan Pesantren Sabilil Muttaqin (YPSM) Mangiran. The research method in this study uses qualitative with a descriptive research type, which is a research procedure or problem-solving that is investigated with a description of the subject or object used in the form of people, institutions, communities and others. The data collection method used was interviews, observation, and documentation. The results of the study show that: 1) The forms of habituation methods in class II MI Kreatif Yayasan Pesantren Sabilil Muttaqin (YPSM) Mangiran are already in the form of routine activities, spontaneous activities, and exemplary activities. 2) The implementation of the habituation method at MI Kreatif Yayasan Pesantren Sabilil Muttaqin (YPSM) Mangiran there are habituation activity programs including: Processing programs in the form of: tahfidz, English for adab and dhuha prayer. General programs in the form of: vegetarian program, Islamic intercourse and marketday program. Keywords: Habituation Method, Responsibility